A broadband and low-power light-control-light effect in a fiber-optic nano-optomechanical system. Issue 17 (24th April 2020) - Zhang, Yu; Zhu, Wenguo; Fan, Pengpeng; He, Yelin; Zhuo, Linqing; Che, Zhen; Li, Dongquan; Zheng, Huadan; Dong, Linpeng; Tang, Jieyuan; Qiu, Wentao; Zhang, Jun; et al.
Abstract : A tapered-nanofibre optomechanical scheme, together with the pump–probe technique, is exploited to implement a broadband and low-power light-control-light effect. Abstract : The coupling of the optical and mechanical degrees of freedom using optical force in nano-devices offers a novel mechanism to implement all-optical signal processing. However, the ultra-weak optical force requires a high pump optical power to realize all-optical processing. For such devices, it is still challenging to lower the pump power and simultaneously broaden the bandwidth of the signal light under processing. In this work, a simple and cost-effective optomechanical scheme was demonstrated that was capable of achieving a broadband (208 nm) and micro-Watt (∼624.13 μW) light-control-light effect driven by a relatively weak optical force (∼3 pN). In the scheme, a tapered nanofiber (TNF) was evanescently coupled with a substrate, allowing the pump light guided in the TNF to generate a strong transverse optical force for the light-control-light effect. Additionally, thanks to the low stiffness (5.44 fN nm −1 ) of the TNF, the light-control-light scheme also provided a simple method to measure the static weak optical force with a minimum detectable optical force down to 380.8 fN. The results establish TNF as a cost-effective scheme to break the limitation of the modulation wavelength bandwidth (MWB) at a low pump power and show that the TNF-optic optomechanical system can be well described as a harmonic oscillator.